Compositions comprising epoxy-functional oxazolidinones
Patent Information
- Application Number
- CN202180082859.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-12
- Filing Date
- 2021-12-06
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-12-06
Smart Images

Figure BDA0004274315380000311 
Figure BDA0004274315380000321
Abstract
Description
[0001] This invention relates to a composition comprising at least (A) at least one epoxy-terminated polyoxazolidinone derived from at least one polyisocyanate compound and at least one aliphatic polyepoxide compound, (B) at least one compound having at least one group reactive to the terminal epoxy group, and (C) at least one solvent, wherein the molar ratio of the epoxy group of the polyepoxide compound to the isocyanate group of the polyisocyanate compound is from 50:1 to 2.4:1, wherein the at least one epoxy-terminated polyoxazolidinone is present in an amount of 50 to 95% by weight, based on the solid content of the composition. The total of all components is 100% by weight based on the solid content of the composition and the solid content of the composition is at least 35% by weight. The method of preparing the composition includes at least the step of mixing components (A), (B), and (C). The use of such a composition as a coating, preferably as an anti-corrosion coating, protective coating, can coating, or coil coating, is involved. A coating formulation containing at least such a composition is involved. A method of coating a substrate includes the step of applying the coating formulation to the substrate. The coating of a substrate containing such a coating formulation is also involved.
[0002] Oxazolidinones are widely used structural building blocks in pharmaceutical applications, and the cycloaddition of epoxides and isocyanates appears to be a convenient one-pot synthetic route. Expensive catalysts, reactive polar solvents, long reaction times, and low chemoselectivity were common in early reports on the synthesis of oxazolidinones (MEDyen and D. Swern, Chem. Rev., 67, 197, 1967). Due to these drawbacks, alternative methods for the production of oxazolidinones are needed, especially for their application as structural building blocks in polymer applications.
[0003] EP 0 113 575 A1 discloses a powder coating composition comprising an epoxy-terminated polyoxazolidinone prepared by reacting a diepoxide with a diisocyanate, wherein the ratio of epoxide equivalent to isocyanate equivalent is from 10:1 to 1.1:1. The resulting polyoxazolidinone has an epoxy equivalent of 250 to 4000.
[0004] EP 3 216 814 A1 discloses an isocyanate-modified epoxy resin and its use as an adhesive or coating with high heat resistance and low dielectric properties. The isocyanate-modified epoxy resin according to the document contains an aromatic moiety in the epoxy portion of the polymer.
[0005] WO 1990 / 015089 A1 discloses epoxy-terminated polyoxazolidinones, methods for their preparation, and electrolaminated components comprising them. The epoxides used in this document are selected from aromatic compounds, such as bisphenol A and / or diglycidyl ethers of tetrabromobisphenol.
[0006] EP 0 113 233 A1 discloses a thermosetting coating composition containing a polyepoxide and a curing agent. It again utilizes aromatic polyepoxides based on bisphenol A and its derivatives.
[0007] The object of the present invention is therefore to provide a coating formulation comprising an epoxy-terminated polyoxazolidinone that advantageously meets the requirements of coatings and is comparable to known coating formulations. A particular object is to provide a corresponding formulation having a solid content of at least 35% by weight to improve the properties of the coating obtained therefrom.
[0008] Surprisingly, it has been discovered that these objectives can be achieved by a composition comprising at least […].
[0009] (A) At least one epoxy group-terminated polyoxazolidinone, derived from at least one polyisocyanate compound and at least one aliphatic polyepoxide compound.
[0010] (B) A compound having at least one group reactive to a terminal epoxy group, and
[0011] (C) At least one solvent,
[0012] The molar ratio of epoxy groups in the polyepoxide compound to isocyanate groups in the polyisocyanate compound is 50:1 to 2.4:1.
[0013] The at least one epoxy-terminated polyoxazolidinone is present in an amount of 50 to 95% by weight, based on the solid content of the composition.
[0014] The total of all components, based on the solid content of the composition, is 100% by weight.
[0015] The composition has a solid content of at least 35% by weight.
[0016] These objectives can be further achieved by a method for preparing the composition, the method comprising at least the step of mixing components (A), (B), and (C), by a composition obtainable by this method, by the use of such a composition as a coating formulation, preferably as an anti-corrosion coating formulation, a protective coating formulation, particularly as a can coating formulation or as a roll coating formulation, by a coating formulation comprising at least such a composition, and by a method for coating a substrate, the method comprising the step of applying such a coating formulation to a substrate, and by the corresponding coating substrate.
[0017] The invention will be explained in detail below:
[0018] As used herein, the term "polyoxazolidinone" is intended to refer to a compound containing at least two oxazolidinone groups in its molecule. The term "epoxy-terminated" polyoxazolidinone refers to a polyoxazolidinone compound in which the molar ratio of the epoxy group of the polyepoxy compound to the isocyanate group of the polyisocyanate compound is from 50:1 to 2.4:1, such that no terminal isocyanate groups are present in the polyoxazolidinone compound used according to the invention.
[0019] The compositions according to the invention comprise at least components (A), (B) and (C), which are explained in detail below.
[0020] Component (A):
[0021] The compositions according to the invention comprise, by weight, 50 to 95% of at least one epoxy group-terminated polyoxazolidinone as component (A), which is derived from at least one polyisocyanate compound and at least one aliphatic polyepoxide compound, based on the solid content of the composition.
[0022] The at least one epoxy group-terminated polyoxazolidinone used according to the present invention is derived from at least one polyisocyanate compound and at least one aliphatic polyepoxide compound.
[0023] The term “polyisocyanate compound” as used in this article is intended to refer to compounds having two or more isocyanate groups.
[0024] In one embodiment of the method according to the invention, the polyisocyanate compound is an aliphatic linear, aliphatic branched, alicyclic, aryliphatic, or aromatic polyisocyanate compound, preferably an aromatic and / or aryliphatic polyisocyanate compound.
[0025] The term “aliphatic linear polyisocyanate compound” as used herein is intended to refer to compounds having two or more isocyanate groups and only an aliphatic linear moiety.
[0026] The term “aliphatic branched polyisocyanate compound” as used herein is intended to refer to a compound having two or more isocyanate groups and an aliphatic branched moiety.
[0027] The term “alicyclic polyisocyanate compound” as used herein is intended to refer to compounds having two or more isocyanate groups and an alicyclic moiety.
[0028] The term “araliphatic polyisocyanate compound” as used in this article is intended to refer to compounds having two or more isocyanate groups and araliphatic moieties.
[0029] The term “aromatic polyisocyanate compound” as used in this article is intended to refer to compounds having two or more isocyanate groups and aromatic moieties.
[0030] In a more preferred embodiment of the method according to the invention, the polyisocyanate compound is an aromatic and / or araliphatic polyisocyanate compound.
[0031] Polyisocyanate compounds and their preparation are generally known to those skilled in the art, for example by phosgenation in the liquid or gas phase or by a phosgenation-free approach, such as by thermal urethane cleavage.
[0032] In one embodiment of the method according to the invention, the polyisocyanate compound is at least one compound selected from polyisocyanates having a molecular weight preferably from 140 to 600 g / mol of a linear aliphatic, branched aliphatic, alicyclic, aryliphatic, and / or aromaticly bonded isocyanate group, examples being 1,4-butane diisocyanate, 1,5-pentane diisocyanate (pentamethylene diisocyanate, PDI), 1,6-hexane diisocyanate (hexamethylene diisocyanate, HDI), 2-methyl-1,5-pentane diisocyanate, 1,5-diisocyanate-2,2-dimethylpentane, 2,2,4- or 2,4,4-trimethyl-1,6-hexane diisocyanate, 1,8-octane diisocyanate, 1,10-decane diisocyanate, 1,1 2-Dodecane diisocyanate, 1,3- and 1,4-cyclohexane diisocyanate, 1,3- and 1,4-bis(isocyanate methyl)cyclohexane, 1-isocyanate methyl-3,3,5-trimethyl-5-isocyanate methylcyclohexane (isophorone diisocyanate, IPDI), 2,4′- and 4,4′-dicyclohexylmethane diisocyanate (H12-MDI), 4,4′-diisocyanate methyl-2,2-dicyclohexylpropane, 1-isocyanate methyl-4(3)isocyanate methylcyclohexane, bis(isocyanate methyl)norbornene, or by means of simple aliphatic straight-chain and / or aliphatic branched and / or alicyclic diisocyanates such as, for example, J. Prakt. Chem. 336 (1994) 185-200, DE-A 1670 666, DE-A 1 954 093, DE-A 2 414 413, DE-A 2 452 532, DE-A 2 641 380, DE-A 3700 209, DE-A 3 900 053 and DE-A 3 928 503 or EP-A 0 336 205, EP-A 0 339 396 and EP-A 0798 As described in 299, for example, any polyisocyanate having a structure of urea diketone, isocyanurate, urethane, biuret, iminooxadiazine diketone and / or oxadiazine triketone, or a mixture of at least two such polyisocyanates, prepared by modification of those of the above types, and 1,3- and 1,4-bis(isocyanate methyl)benzene (phenylenedimethyl diisocyanate, XDI), 1,3- and 1,4-bis(2-isocyanate propyl-2-yl)benzene (tetramethyl) Benzene dimethyl diisocyanate (TMXDI), 1,3-bis(isocyanate methyl)-4-methylbenzene, 1,3-bis(isocyanate methyl)-4-ethylbenzene, 1,3-bis(isocyanate methyl)-5-methylbenzene, 1,3-bis(isocyanate methyl)-2,4,6-trimethylbenzene, 1,3-bis(isocyanate methyl)-4,5-dimethylbenzene, 1,4-bis(isocyanate methyl)-2,5-dimethylbenzene, 1,4-Bis(isocyanate methyl)-2,3,5,6-tetramethylbenzene, 1,3-bis(isocyanate methyl)-5-tert-butylbenzene, 1,3-bis(isocyanate methyl)-4-chlorobenzene, 1,3-bis(isocyanate methyl)-4,5-dichlorobenzene, 1,3-bis(isocyanate methyl)-2,4,5,6-tetrachlorobenzene, 1,4-bis(isocyanate methyl)-2,3,5,6-tetrachlorobenzene, 1,4-bis(isocyanate methyl)-2,3,5,6-tetrabromobenzene, 1,4-bis(2-isocyanate ethyl)benzene and 1,4-bis( (Isocyanate-methyl)naphthalene, 1,2-, 1,3- and 1,4-diisocyanate-phenylene (phenylene diisocyanate), 2,4- and 2,6-diisocyanate-toluene (toluene diisocyanate, TDI), 2,3,5,6-tetramethyl-1,4-diisocyanate-phenylene, isomeric diethylphenylene diisocyanate, diisopropylphenylene diisocyanate, diisododecylphenylene diisocyanate and biphenyl diisocyanate, 3,3′-dimethoxybiphenyl-4,4′-diisocyanate, 2,2′-, 2,4′- and 4,4′-diphenylmethane diisocyanate (MDI), 3... 3′-Dimethyldiphenylmethane-4,4′-diisocyanate, 4,4′-diphenylethane diisocyanate, 1,5-naphthalene diisocyanate (NDI), diphenyl ether diisocyanate, ethylene glycol diphenyl ether diisocyanate, diethylene glycol diphenyl ether diisocyanate, 1,3-propanediol diphenyl ether diisocyanate, benzophenone diisocyanate, benzene triisocyanate, 2,4,6-toluene triisocyanate, trimethylbenzene triisocyanate, diphenylmethane-2,4,4′-triisocyanate, 3-methyldiphenylmethane-4,6,4′-triisocyanate, isomeric naphthalene triisocyanate, and methylnaphthalene Diisocyanates, triphenylmethane triisocyanates, 2,4-diisocyanate-1-[(5-isocyanate-2-methylphenyl)methyl]benzene, 4-methyl-diphenylmethane-3,5,2′,4′,6′-pentaisocyanates, and polynuclear homologues of diphenylmethane diisocyanates referred to as "polymer-MDI," as well as polyisocyanates having urethane and / or isocyanurate structures obtainable from monomers 2,4- and / or 2,6-TDI through reaction with polyols and / or oligomerization, preferably trimerization, which can be obtained, for example, through DE-A Obtained by any known method described in 870400, DE-A 953 012, DE-A 1 090 196, EP-A 0 546 399, CN 105218780, CN 103881050, CN101717571, US 3 183 112, EP-A 0 416 338, EP-A 0 751 163, EP-A 1 378 529, EP-A 1378 530, EP-A 2 174 967, JP 63260915, or JP 56059828.Or mixtures of at least two such polyisocyanates, and those polyisocyanate compounds with aromatic and aliphatic straight-chain or branched isocyanate groups, such as mixed trimers or urethane esters of 2,4- and / or 2,6-TDI with HDI as described in DE-A 1 670 667, EP-A 0 078 991, EP-A 0 696 606 and EP-A 0807 623.
[0033] According to the present invention, a mixture of two or more of the above-described polyisocyanate compounds may also be used.
[0034] Particularly preferably, the at least one polyisocyanate compound is selected from at least one compound selected from 2,2′-, 2,4′- and 4,4′-diphenylmethane diisocyanate (MDI), polynuclear homologues of diphenylmethane diisocyanate known as “polymer-MDI”, 2,4- and 2,6-toluene diisocyanate (toluene diisocyanate, TDI), 1,3- and 1,4-bis(isocyanate-methyl)benzene (phenylenediethylene diisocyanate, XDI), 1,3- and 1,4-bis(2-isocyanate-propyl-2-yl)benzene (tetramethylphenylenediethylene diisocyanate, TMXDI), 3,3′-dimethyldiphenylmethane-4,4′-diisocyanate, 4,4′-diphenylethane diisocyanate, 1,5-naphthalene diisocyanate (NDI), and mixtures thereof.
[0035] The at least one epoxy group-terminated polyoxazolidinone used according to the present invention is further derived from at least one aliphatic polyepoxide compound.
[0036] As used in this article, the term "polyepoxide" refers to a compound having two or more epoxide groups.
[0037] According to the present invention, at least one aliphatic polyepoxide compound is used. The term "aliphatic polyepoxide compound" as used herein is intended to mean a compound having two or more epoxide groups and containing only an aliphatic linear or branched moiety and / or an alicyclic moiety.
[0038] In a preferred embodiment of the present invention, the at least one aliphatic polyepoxide compound is selected from neopentyl glycol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, 1,4-cyclohexanedicarboxylic acid diglycidyl ester, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol triglycidyl ether, polyglycerol polyglycidyl ether, ethoxylated trimethylolpropane polyglycidyl ether, poly(tetramethylene-oxid)diglycidyl ether. The following are compounds derived from the epoxidation of pentaerythritol polyglycidyl ether, vinylcyclohexene diepoxide, diepoxides of C1 to C18 alkyl esters of diunsaturated fatty acids, polyepoxides of diunsaturated ethoxylated fatty alcohols, and aliphatic di- or polyglycidyl ethers derived from the epoxidation of di- or polyfunctional alcohols having an aliphatic straight chain, aliphatic branched or alicyclic moiety consisting of 2 to 40 carbon atoms, such as ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, octanediol diglycidyl ether, trimethylolpropane polyglycidyl ether, glycerol polyethylene triglycidyl ether, 2-ethylhexyl diglycidyl ether, and isosorbide diglycidyl ether.
[0039] In a more preferred embodiment of the invention, the at least one aliphatic polyepoxide compound is selected from at least one compound of hydrogenated bisphenol A diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol triglycidyl ether, ethoxylated trimethylolpropane polyglycidyl ether, poly(tetramethylene-oxy) diglycidyl ether, pentaerythritol polyglycidyl ether, diepoxides of C1 to C18 alkyl esters of diunsaturated fatty acids, and aliphatic di- or polyglycidyl ethers derived by epoxidation of a di- or polyfunctional alcohol having an aliphatic straight chain, aliphatic branched or alicyclic moiety consisting of 2-40 carbon atoms, such as ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane polyglycidyl ether, glycerol polyethylene triglycidyl ether, 2-ethylhexyl diglycidyl ether, and isosorbide diglycidyl ether.
[0040] Most preferably, the at least one aliphatic polyepoxide compound is selected from at least one compound of ethylene glycol diglycidyl ether, butylene glycol diglycidyl ether, hexanediol diglycidyl ether, and trimethylolpropane triglycidyl ether.
[0041] A mixture of two or more of the above-mentioned aliphatic polycyclic oxides may also be used.
[0042] Component (A) of the composition according to the invention is obtained by reacting at least one polyisocyanate compound and at least one aliphatic polyepoxide compound (both as described above).
[0043] In a preferred embodiment of the invention, component (A) is a product of at least one aryl aliphatic polyisocyanate compound and at least one aliphatic polyepoxide compound.
[0044] In another preferred embodiment of the invention, component (A) is a product of at least one aromatic polyisocyanate compound and at least one aliphatic polyepoxide compound.
[0045] Generally, the reaction between the at least one polyisocyanate compound and the at least one aliphatic polyepoxide compound can be carried out by any method known to those skilled in the art.
[0046] In a preferred embodiment of the invention, the molar ratio of the epoxy group of the at least one aliphatic polyepoxide compound to the isocyanate group of the at least one polyisocyanate compound is 50:1 to 2.5:1, particularly preferably 25:1 to 2.5:1, more preferably 10:1 to 2.5:1, further preferably 7:1 to 2.6:1, more preferably 6:1 to 2.6:1, and even more preferably 5:1 to 2.6:1.
[0047] A preferred method for preparing component (A) includes the following steps:
[0048] i) Mix the at least one polyisocyanate compound, the at least one polyepoxide compound, and at least one catalyst to form mixture (i);
[0049] ii) Copolymerize the mixture (i).
[0050] An alternative method includes the following steps:
[0051] iii) Mix the at least one polyepoxide compound and at least a portion of at least one catalyst to form mixture (iii);
[0052] iv) Add the at least one polyisocyanate compound to the mixture (iii) under copolymerization conditions.
[0053] Another alternative method includes the following steps:
[0054] v) Mix the at least one polyisocyanate compound and at least a portion of the at least one catalyst to form a mixture (v);
[0055] vi) Add at least one polyepoxide compound to mixture (v) under copolymerization conditions.
[0056] Suitable conditions for this copolymerization method are, for example, a reaction temperature of 130 to 280°C, preferably 140 to 240°C, more preferably 155 to 210°C, and most preferably 165 to 195°C. If the temperature is set below 130°C, the reaction is typically very slow. At temperatures above 280°C, the amount of undesirable byproducts increases significantly.
[0057] The catalyst is typically selected from LiCl, LiBr, LiI, MgCl2, MgBr2, MgI2, SmI3, Ph4SbBr, Ph4SbCl, Ph4PBr, Ph4PCl, Ph3(C6H4-OCH3)PBr, Ph3(C6H4-OCH3)PCl, Ph3(C6H4F)PCl, and Ph3(C6H4F)PBr, preferably at least one compound from LiCl, LiBr, LiI, and MgCl2.
[0058] The catalyst is typically present in a molar amount of 0.001 to 2.0 mol% based on the at least one polyepoxide compound, preferably 0.005 to 1.5 mol%, more preferably 0.01 to 1.0 mol%.
[0059] The catalyst or a solution of the catalyst in the solvent is added in one or more parts to ensure homogeneous dissolution. Suitable solvents are, for example, organic solvents such as straight-chain or branched alkanes or mixtures of alkanes, monosubstituted or polysubstituted halogenated aromatic solvents or halogenated alkane solvents, such as 1,2-dichlorobenzene, straight-chain or cyclic esters, or polar aprotic solvents such as cyclic carbonates, such as ethylene carbonate or propylene carbonate, N-methylpyrrolidone (NMP), sulfolane, tetramethylurea, N,N′-dimethylethyleneurea, or the above solvents and / or mixtures with other solvents.
[0060] The copolymerization can be carried out with or without a solvent.
[0061] According to the present invention, the epoxy group-terminated polyoxazolidinone (A) preferably has an epoxy equivalent weight (EEW) of 100 to 5000 g / eq, more preferably 150 to 3000 g / eq, and more preferably 200 to 1500 g / eq, wherein the epoxy equivalent weight is measured using a Metrohm 888 Titrando system. An epoxy sample (0.4-0.7 g) is dissolved in glacial acetic acid (50 mL) in a 250 mL beaker. Subsequently, tetrabutylammonium bromide (TBAB) is dissolved in glacial acetic acid (0.2 mol·L⁻¹). -1 A solution in 25 mL was added to the dissolved epoxy sample. This solution was prepared with a solution of perchloric acid in glacial acetic acid (0.1 mol·L⁻¹). -1 Titrate until the equivalence point.
[0062] The at least one epoxy-terminated polyoxazolidinone (A) used in the compositions according to the invention is present in the composition in an amount of 50 to 95% by weight, preferably 65 to 95% by weight, particularly preferably 70 to 90% by weight, in each case based on the solid content of the composition. The total of all components in each case is 100% by weight based on the solid content of the compositions according to the invention.
[0063] The epoxy-terminated polyoxazolidinone typically has an oxazolidinone weight content of 5 to 50% by weight, preferably 7 to 45% by weight, and particularly preferably 10 to 40% by weight. This content is calculated from the amount of at least one polyisocyanate and at least one epoxy compound used to prepare the epoxy-terminated polyoxazolidinone, wherein the oxazolidinone group has a molecular weight of 86.07 g / mol. These calculations are based on a basic 100% conversion. The conversion and selectivity of the reaction for oxazolidinone are measured and confirmed using analytical methods known to those skilled in the art, such as IR (infrared spectroscopy) and / or 13C-NMR spectroscopy.
[0064] The present invention therefore preferably relates to compositions according to the invention, wherein the epoxy group-terminated polyoxazolidinone typically has a weight content of 5 to 50% by weight, preferably 7 to 45% by weight, and particularly preferably 10 to 40% by weight of oxazolidinone.
[0065] The composition according to the invention comprises at least one compound having at least one functional group that is reactive to a terminal epoxy group as component (B).
[0066] Generally, component (B) present in the composition according to the invention can be any compound containing at least one functional group that is reactive to the terminal epoxy group of component (A).
[0067] Component (B) present in the composition according to the invention is a curing agent, i.e., a hardening agent or crosslinking agent, or a blend of curing agents. Generally, any curing agent known in the art suitable for curing epoxy resins can be used. The choice of curing agent may depend on the application requirements.
[0068] Preferably, component (B) is selected from dicyandiamide, substituted guanidine, phenolic compounds, amines (especially aliphatic amines), benzoxazine, acid anhydrides, aminoamines, polyamides, polyamines, polyesters, polyisocyanates, polythiols, urea-formaldehyde, melamine-formaldehyde resins and mixtures thereof.
[0069] For example, in one embodiment, component (B) is at least one acid anhydride or a mixture containing at least one acid anhydride group. Examples of corresponding preferred components (B) are selected from phthalic anhydride and derivatives, nadic acid anhydride and derivatives, trimellitic anhydride and derivatives, pyromellitic anhydride and derivatives, benzophenone tetracarboxylic anhydride and derivatives, dodecenyl succinic anhydride and derivatives, poly(ethyl octadecanoic acid) anhydride and derivatives, and mixtures thereof.
[0070] In one embodiment, component (B) is at least one amine. Preferred amines are selected from aliphatic amines, particularly ethanolamine, ethylenediamine, diethylenetriamine (DETA), triethylenetetramine (TETA), dicyandiamide or amine-terminated polyols, aromatic amines, particularly 1-(o-tolyl)-biguanide, methylene diphenylamine (MDA), toluenediamine (TDA), diethyltoluenediamine (DETDA) or diaminodiphenyl sulfone (DADS) and mixtures thereof.
[0071] Thiols, especially thiol-terminated polysulfide polymers or mixtures thereof, may also be used as component (B).
[0072] The trimellitic anhydride-based system is optimally used as component (B).
[0073] Another group of preferred compounds used as component (B) in the compositions according to the invention are phenolic compounds, including but not limited to reaction products of aldehydes and phenols. Examples of aldehydes include, but are not limited to, formaldehyde and acetaldehyde. Various phenols can be used, such as, but not limited to, phenol, cresol, p-phenylphenol, p-tert-butylphenol, p-tert-amylphenol, cyclopentylphenol, toluene, bisphenol-A, bisphenol-F, and combinations thereof. Examples of commercially available phenolic crosslinking agents are, for example, Aradur 949-2 available from HUNTSMANN and PHENODUR available from CYTEC Industries. TM PR 612, etc. Acid-functionalized phenols can also be used to manufacture phenolic resins. The corresponding component (B) can be unetherified or etherified with alcohol or polyol.
[0074] According to a particularly preferred embodiment of the invention, the at least one compound in component (B) comprising at least one functional group reactive to a terminal epoxy group is selected from acid anhydrides, phenolic compounds, amines, benzoxazines, aminoamines, polyamides, polyamines, and mixtures thereof.
[0075] The at least one compound having at least one functional group reactive to a terminal epoxy group (component (B)) is present in the composition in an amount of 5 to 50% by weight, preferably 5 to 35% by weight, particularly preferably 10 to 30% by weight, in each case based on the solid content of the composition.
[0076] According to a preferred embodiment of the present invention, the weight ratio of the epoxy group of component (A) to the functional group of component (B) that is reactive to the terminal epoxy group is 50:50 to 95:5; preferably 60:40 to 90:10, more preferably 65:35 to 85:15.
[0077] The composition according to the invention comprises at least one solvent as component (C).
[0078] The at least one solvent present in the composition according to the invention is generally selected from any organic solvent and mixture of organic solvents known to those skilled in the art.
[0079] The at least one solvent is preferably selected from aromatic hydrocarbons, such as toluene, xylene, or Solvesso 100; ketones, such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), methyl propyl ketone, isophorone ethylpentyl ketone, or methyl n-pentyl ketone; alcohols, such as butanol, n-hexanol, pentanol, 2-ethylhexanol, or cyclohexanol; ether alcohols and their acetate esters, such as methoxyethanol, ethoxyethanol, butoxyethanol, hexoxyethanol, methoxypropanol, methoxyethyl acetate, or ethoxyethyl acetate, methoxypropyl acetate (MPA); cyclic ethers, such as tetrahydrofuran (THF); ureas, such as dimethyl propylene urea (DMPU) and mixtures thereof, and at least one organic solvent.
[0080] The at least one solvent (component (C)) is present in the composition in an amount of 5 to 75% by weight, preferably 15 to 70% by weight, particularly preferably 30 to 65% by weight, in each case as the sum of components (A), (B) and (C) of the composition.
[0081] Optionally, in addition to components (A), (B), and (C), the composition according to the invention may contain at least one additive as component (D). An example of such additive is phosphoric acid.
[0082] The at least one additive may be added in an amount of 0.1% to 5%, preferably 0.1% to 2%, and most preferably 0.5% to 1.5% of the sum of components (A), (B), (C) and (D).
[0083] The present invention further relates to a method for preparing a composition according to the invention, which includes at least the step of mixing components (A), (B) and (C).
[0084] Generally, the compositions according to the invention can be prepared using any method known to those skilled in the art. In particular,
[0085] Preferably, component (A) is added to a suitable reactor, such as a glass bottle, and diluted with solvent component (C). Then, preferably, a corresponding amount of component (B), which is also preferably dissolved in the solvent (component (C)), is added to the solution. Optionally, an additive (component (D)) may then be added.
[0086] The present invention further relates to compositions obtainable by the method according to the invention.
[0087] The present invention further relates to the use of the compositions according to the invention as coating formulations.
[0088] The coating formulations mentioned are generally known to those skilled in the art. Depending on the specific application of the coating formulation, additional components may be optionally present in the specific formulation, in addition to the fully described components (A), (B), and (C).
[0089] Therefore, in addition to components (A), (B), and (C) present in the compositions according to the invention, the coating formulations according to the invention may also contain at least one additive. Generally, the at least one additive may be selected from any additive known to those skilled in the art of coating formulation.
[0090] Preferably, the at least one additive is selected from thermally decomposable salts with no or substantially no residue, preferably physically curable, thermosetting and / or photocurable adhesives, crosslinking agents, organic solvents other than the at least one solvent mentioned as component (C), thermosetting reactive diluents, photocurable reactive diluents, coloring and / or effect pigments, transparent pigments, fillers, molecularly dispersible dyes, nanoparticles, light stabilizers, antioxidants, degassing agents, emulsifiers, slip additives, polymerization inhibitors, free radical polymerization initiators, thermally unstable free radical initiators, adhesion promoters, leveling agents, film-forming aids, such as thickeners and shear-thinning sagging control agents (SCA), flame retardants, corrosion inhibitors, flow aids, and drying agents. Drying agents, biocides, matting agents, organic pigments, inorganic pigments such as zinc oxide, carbon black, or titanium dioxide anti-corrosion pigments, fillers such as calcium sulfate, barium sulfate, silicates such as talc, bentonite, kaolin, and silicon dioxide, oxides such as aluminum hydroxide and magnesium hydroxide, nanoparticles, organic fillers such as textile fibers, cellulose fibers, polyethylene fibers, wood flour, titanium dioxide, carbon black, iron oxide, zinc phosphate, and lead silicate, free radical scavengers, organic corrosion inhibitors, crosslinking catalysts such as inorganic and organic salts and complexes of tin, lead, antimony, bismuth, iron, or manganese, preferably organic salts and complexes of bismuth and tin, especially bismuth lactate, bismuth ethylhexanoate or bismuth dimethylolpropionate, dibutyltin oxide or dibutyltin dilaurate, polymerization inhibitors, and defoamers. Film-forming agents, emulsifiers, such as nonionic emulsifiers like alkoxylated alkanols and polyols, phenols and alkylphenols, or anionic emulsifiers like basic or ammonium salts of alkanic acids, basic or ammonium salts of alkanic sulfonic acids, and basic or ammonium salts of alkoxylated alkanols and polyols, phenols and alkylphenols sulfonic acids; wetting agents, such as siloxanes, fluorinated compounds, carboxylic acid half esters, phosphate esters, polyacrylic acid and its copolymers or polyurethanes; adhesion promoters; flow aids; film-forming aids, such as cellulose derivatives; flame retardants; low molecular weight, oligomeric and high molecular weight reactive diluents that can participate in thermal crosslinking, such as polyols like tricyclodecanediethanol, dendritic polyols, hyperbranched polyesters, polyols based on metathesis oligomers or branched alkanes having more than 8 carbon atoms in the molecule. The following substances are permitted: alcohols, anti-cratering agents, water-miscible or water-dispersible organic solvents, rheology control additives, crosslinked polymer particles, inorganic layered silicates, preferably montmorillonite, especially montmorillonite and lithium montmorillonite, such as magnesium aluminum silicate, sodium-magnesium and sodium-magnesium-fluorine-lithium layered silicates of the montmorillonite type, or inorganic layered silicates such as magnesium aluminum silicate, sodium-magnesium and montmorillonite-type sodium-magnesium-fluorine-lithium layered silicates, silica such as aerorosils, synthetic polymers with ionic and / or associative groups, such as polyvinyl alcohol, poly(meth)acrylamide, poly(meth)acrylic acid, polyvinylpyrrolidone, styrene-maleic anhydride or ethylene-maleic anhydride copolymers and their derivatives or hydrophobically modified polyacrylates, associative polyurethane thickeners, and catalysts.For example, hydrophobic sulfonic acid catalysts based on dinonylnaphthalene disulfonic acid are preferably supplied as a solution in isobutanol (Nacure 155), alcohols such as butanol or hexanol, stabilizers such as phosphoric acid, and mixtures thereof. Suitable additives of the above type are known, for example, from German patent applications DE 199 48 004 A1, DE 199 14 98 A1, and DE100 43 405 C1.
[0091] The coating compositions according to the invention typically contain the above-mentioned additives or mixtures thereof in amounts commonly used in the art. Preferably, the additives are used in an amount of 0.1 to 5% by weight based on the total amount of the coating formulation.
[0092] The present invention further relates to coating formulations comprising at least one composition according to the invention. Preferably, the invention relates to preferred formulations as described above comprising the preferred components. Furthermore, optional additives as mentioned are also suitable for coating formulations according to the invention.
[0093] The present invention further relates to a method of coating a substrate, comprising the step of applying a coating formulation according to the invention onto the substrate.
[0094] Examples of suitable substrates include beverage cans, food cans, aerosol containers such as those used for non-food products like hairspray, hair dye, or color spray paint, drums, kegs, bags, decorative tins, open trays, tubes, bottles, monoblocs, caps, lids such as foil-based lids for yogurt and butter containers, or crown corks, and closures for glass jars and bottles such as roll-on closures, vacuum closures, pilfer-proof closures, easy-peel lids for can closures, and easy-open ends or conventional end caps for cans. Cans to which the coating compositions disclosed herein can be applied can be two-piece or three-piece cans.
[0095] Beverage cans include, but are not limited to, beer cans, carbonated soft drink cans, energy drink cans, isotonic beverage cans, water cans, juice cans, tea cans, coffee cans, and milk cans.
[0096] Food cans include, but are not limited to, vegetable cans, fruit cans, meat cans, soup cans, ready-to-eat meal cans, fish cans, cooking oil cans, and sauce cans. These cans can have various shapes, such as cylindrical, cubic, spherical, hemispherical, bottle-shaped, elongated cubic, shallow or tall, circular or rectangular, or other suitable shapes, or combinations thereof.
[0097] The substrate itself preferably comprises a metal, such as a metallic substrate. Examples of metals include, but are not limited to, aluminum and aluminum alloys, steel, electrolytic tin-coated cold-rolled low-carbon mild steel, electrolytic chromium / chromium oxide-coated cold-rolled low-carbon mild steel, and other pretreated steels. Pretreatment may include, but is not limited to, treatment with phosphoric acid, zirconium phosphate, chromium phosphate, etc., and silanes for, for example, primary corrosion protection and improved adhesion. The metallic substrate may include sheets, strips, or coils.
[0098] The substrate can be formed by stamping, drawing, redrawing, wall ironing, bending, crimping, embossing, debossing, flanging, necking, stretching, blow drawing and / or other suitable conventional methods. These methods are known to those skilled in the art.
[0099] According to the present invention, a coating composition may be applied, for example, to a substrate, such as a metal sheet or metal foil, and then the coating may be cured. The coated substrate may then be shaped into a coated article, such as a container device or a coated closure device.
[0100] According to another embodiment of the invention, a substrate can be molded into a container, such as a container device or a sealing device, which can then be coated with a coating composition, and the coating can then be cured to form a coated article.
[0101] In various embodiments, the coating formulation can be applied by a variety of methods, such as brushing, roller coating, spraying (e.g., air atomization spraying, air spraying, airless spraying, high-volume low-pressure powder coating), dip coating, electrodeposition coating (e.g., electrostatic bell application), all printing methods (e.g., screen printing, letterpress printing, gravure printing, offset printing, flexographic printing, pad printing, embossing, debossing, thermal and digital printing), wash coating, flow coating, flood coating, draw-down coating, knife or scraper coating, slot dye coating, and / or curtain coating. Manual or automatic methods can be used.
[0102] The curing step is preferably carried out at a temperature of 20 to 250°C, more preferably 100 to 250°C, and particularly preferably 110 to 210°C. The curing step is preferably carried out for 7 to 40 minutes, and particularly preferably 10 to 20 minutes. Those skilled in the art will select the curing temperature and / or curing time based on the chemical properties of component (B).
[0103] A coating, i.e., a coating composition applied to a substrate, can have a thickness of 0.01 to 2000 μm. All individual values and sub-ranges of 0.01 to 2000 μm are included and disclosed herein; for example, a coating can have a thickness from a lower limit of 0.01 μm, 0.05 μm, or 1 μm to an upper limit of 2000 μm, 1500 μm, or 1000 μm. For example, a coating can have a thickness of 0.01 to 2000 μm, 0.05 to 1500 μm, or alternatively, 0.1 to 1000 μm. According to a preferred embodiment, a coating can have a thickness of 5 to 500 μm.
[0104] The present invention further relates to coating substrates comprising coating formulations according to the present invention. Example
[0105] The invention will be further described with reference to the following embodiments, but it is not intended to be limited thereto.
[0106] The following chemicals and compounds are used:
[0107] diisocyanate compounds
[0108] MDI: Diphenylmethane diisocyanate ( VP.PU 1806), >99% by weight, Covestro AG, Germany.
[0109] pMDI: 44V10L, a mixture of diphenylmethane diisocyanate (MDI) with isomers and homologues of higher functionality, with an NCO content of 30.5 to 32.5% by weight.
[0110] Epoxy compounds
[0111] DY-D / CH: Butylene glycol diglycidyl ether (BDDE), EEW 118 to 125 g / eq; obtained from HUNTSMAN Advanced Materials (Deutschland) GmbH, Germany. DY-D / CH provides a large number of compounds that are not ideally structured, but for example, BDDE, the effective molar amount of the epoxy group is calculated based on the experimentally determined EEW 121 g / eq.
[0112] ipox RD 20: Trimethylolpropane polyglycidyl ether, EEW 140 to 150 g / eq, obtained from ipoxchemicals GmbH, Germany. Since ipox RD 20 provides a large number of compounds with non-ideal structures, but such as trimethylolpropane polyglycidyl ether, the effective molar amount of epoxy groups was calculated based on an experimentally determined EEW of 149 g / eq.
[0113] BDDE: 1,4-Butanediol diglycidyl ether: obtained from Merck, purity >= 95%
[0114] TMPGE: Trimethylolpropane triglycidyl ether: Technical grade from Merck
[0115] Aradur 949-2: Butylated bisphenol A methyl phenolic resin, obtained from HUNTSMANA Advanced Materials (Deutschland) GmbH, Germany. Epoxy curing agent. Bisphenol A-based etherified methyl phenolic resin supplied in n-butanol. Epoxy equivalent weight 1500-2000.
[0116] Aradur 3380-1 CH: A modified anhydride hardener from HUNTSMAN Advanced Materials (Deutschland) GmbH, Germany. A low-molecular-weight acid hardener used in epoxy can coatings and powder coatings. Acid value 500-540 mg KOH / g, anhydride content 3.00-4.00 eq / kg.
[0117] catalyst
[0118] LiCl, lithium chloride, purity >99% by weight, obtained from Sigma Aldrich, Germany.
[0119] LiBr lithium bromide, purity >99% by weight, obtained from Sigma Aldrich, Germany.
[0120] Ph4PBr Tetraphenylphosphonium bromide, 97% by weight, obtained from Sigma Aldrich, Germany.
[0121] Ph4PCl tetraphenylphosphonium chloride, 98% purity, obtained from Sigma Aldrich, Germany.
[0122] solvent
[0123] MPA 1-methoxypropyl-2-acetic acid ester, anhydrous, obtained from Azelis, St. Augustin.
[0124] Toluene is from Azelis, St. Augustin.
[0125] n-Butanol was obtained from Kraemer and Martin, St. Augustin.
[0126] Methoxypropanol was obtained from Kraemer
[0127] Phosphoric acid purity 85%, obtained from Riedel-de Haen.
[0128] DMPU 1,3-Dimethyl-3,4,5,6-Tetrahydro-2(1H)-pyrimidinone, purity >99% by weight, anhydrous, obtained from Sigma Aldrich, Germany.
[0129] CPC cyclic propylene carbonate, purity >99% by weight, anhydrous, obtained from Sigma-Aldrich, Germany.
[0130] Add a solution
[0131] Batch method: Weigh all components into a glass flask, place it in an oil bath preheated to 175°C and stir immediately.
[0132] Semi-batch process: A diepoxide or a mixture of diepoxides is provided in a glass flask and heated to 175°C under argon. The catalyst or a solution of the catalyst in the solvent is added in one step. The diisocyanate compound or a mixture of diisocyanates is slowly added to the reactor while the mixture is continuously stirred at 175°C.
[0133] Characterization methods:
[0134] Infrared spectroscopy
[0135] IR analysis was performed on a Bruker ALPHA-P IR spectrometer equipped with a diamond probe. OPUS 6.5 software was used for data processing. Background spectra were recorded against ambient air. Subsequently, small samples (2 mg) of the polyoxazolidinone prepolymer were applied to the diamond probe, and infrared spectra were recorded from 4000 to 400 cm⁻¹. -1 Within a range of 4cm -1 The average was obtained from 24 spectra at a resolution of [resolution value missing].
[0136] GPC
[0137] In tetrahydrofuran (THF, flow rate: 1.0 mL·min) -1GPC measurements were performed at 40°C. The column assembly consisted of three consecutive columns (PSS SDV, 5 μm, 8 x 50 mm pre-column, and 2PSS SDV linear S, 5 μm, 8 x 300 mm). Samples (concentrations of 2 to 3 g·L⁻¹) were injected using an Agilent Technologies 1200 Series autosampler. -1 The injection volume was 20 μL. Concentration at the column outlet was tracked using an Agilent 1200 series RID detector. Raw data were processed using the PSS WinGPC Unity software package. A known molecular weight of polystyrene was used as a reference to calculate the molecular weight distribution (using the PSS ReadyCal Kit in the range of 266 to 66,000 Da). The number-average molecular weight measured by GPC is specified as Mn(GPC) in the examples.
[0138] Viscosity
[0139] Viscosity values were determined using a cone / plate rheometer from Anton Paar MCR 302. A viscosity of 631 min was used. -1 The viscosity of the product was determined by the shear rate. Viscosity is given in mPa·s. (Following the procedure according to DIN EN ISO 3219 / A.3:1994). Unless otherwise specified, all measurements were performed at 25°C.
[0140] Gardner Color Index
[0141] Gardner color index was determined using a Lico 620 from Hach. Therefore, the sample of the product mixture was diluted with N,N-dimethylacetamide (50:50) to reduce viscosity. The sample solution was then filled into cuvettes and analyzed according to DIN EN ISO 1557:1997.
[0142] Epoxy Equivalent Weight (EEW)
[0143] The epoxide equivalent weight was measured using a Metrohm 888 Titrando system. The epoxide sample (0.4 to 0.7 g) was dissolved in glacial acetic acid (50 mL) in a 250 mL beaker. Subsequently, tetrabutylammonium bromide (TBAB) was dissolved in glacial acetic acid (0.2 mol·L⁻¹). -1 A solution in 25 mL was added to the dissolved epoxy sample. This solution was prepared with a solution of perchloric acid in glacial acetic acid (0.1 mol·L⁻¹). -1 Titrate until the equivalence point.
[0144] rocker arm damping
[0145] According to DIN EN ISO 1522:2007-04, the determination was performed on a glass plate. The swing arm damping.
[0146] Solvent resistance
[0147] To test the solvent resistance of the coating, small amounts of each solvent—xylene, 1-methoxypropyl-2-acetate, ethyl acetate, and acetone—were placed in test tubes with cotton pads at the openings, thus creating a solvent-saturated atmosphere within the test tubes. The test tubes were then pressed onto the coating surface through the cotton pads, where they remained for 5 minutes. After the solvents were wiped off, the damage / softening / adhesion loss of the film was examined and rated (0 = no change, 5 = complete film dissolution). The reported evaluation results are in the form of four consecutive numbers, representing the evaluation results of the four solvents in the order of xylene (X), 1-methoxypropyl-2-acetate (MPA), ethyl acetate (EA), and acetone (A) under each condition. These were determined according to DIN EN ISO 4628-1:2016-07.
[0148] In addition, solvent resistance was tested by counting the number of double rubbing (i.e., forward and backward) cycles required to remove the coating to expose the metal. A piece of cotton lint soaked in methyl ethyl ketone (MEK) was used for rubbing. Results were reported as 0 to 100 cycles, with cycles higher than 100 reported as >100.
[0149] Chemical resistance
[0150] To test the coating's chemical resistance to water, acids, and alkalis, different methods were used. A 10% by weight NaOH solution and a sulfuric acid solution were deposited on the coating and covered with a small glass bottle. Cotton pads were soaked in water and then placed on the coating, followed by covering with a small glass bottle. The solutions remained on the coating for 24 hours. Afterward, the chemicals were removed from the coating using fresh water. The panel was then dried with paper, and the visible changes were first examined, followed by scratching the surface with a fingernail. Observations were graded as follows: 0: no change; 1: small rings observed; 5: the film completely dissolved without fingernail scratches. These were determined according to DIN EN ISO 4628-1:2016-07.
[0151] Stack strength
[0152] To determine the stacking strength of the coating, square instrument panels (10cm x 10cm) made of tinplate were used as the substrate. A 55mm ring of filter paper (“black ribbon”) from Schleicher and Schuell was placed on the coating, and a second panel was placed face down on top of it. A 10cm metal plate was placed on top of these coated panels, followed by a 5kg weight. This setup was placed in an oven at 50°C for 16 hours. After the test, the panels were removed from the oven and separated. The results were based on the visual test report regarding the number of fibers observed on the coated panels. The panels were rated from 0 to 5, where 0 indicates no visible effect on the coating surface and 5 indicates that the filter paper was not easily removed from the coating.
[0153] Adhesion (“Gitterschnitt”)
[0154] Adhesion was checked by creating a 1mm square cross-cut grid (9x9) on the panel. The panel was then impacted from a height of 30 inches with an Erickson ball from the uncoated side. The grid was then covered with clear tape and removed twice. Afterward, the panel was immersed in a solution of 10% copper sulfate and 10% HCl for several seconds. This allowed for better observation of coating changes, as the copper color indicates coating removal. Results were reported on a scale of 0 to 5, where 0 indicates no effect on the coating and 5 indicates complete removal of the coating from the panel.
[0155] wedge bend
[0156] A wedge bending test was performed to determine flexibility, after the panel had been aged at room temperature for at least one day. The cooled panel (100mm x 40mm) was bent on a 5mm cylindrical mandrel. The resulting folded panel was then impacted (9N) in a device (wedge bending tester, Erichsen model 471) to form a wedge profile, flat at one end and 6mm in diameter at the other. The sample was then immersed in a 10% wt% copper sulfate / 10% wt% hydrochloric acid aqueous solution for several seconds. This stains any cracks that appear in the coating. The width of the crack surface (in centimeters) was measured starting from the flat side; a larger value indicates greater damage to the coating.
[0157] Sterilization test
[0158] This is achieved by first stretching the panel into a bent shape of approximately 300°.
[0159] Perform a sterilization test. Place the coated panel in a sterilizer at 121°C in the presence of water for 1 hour. Then rapidly cool the panel to 50–60°C over 15 minutes and remove it from the machine. Wipe the panel dry with paper and immediately assess for bubbles, whitening, and coating removal from the panel. Also, scratch the surface with a fingernail to determine the damage to the coating. Results are reported on a scale of 0 to 5, where 0 indicates no change observed and 5 indicates complete coating failure.
[0160] reactor
[0161] The reaction was carried out in a 500 mL or 1000 mL three-necked round-bottom flask under a continuous argon flow. A syringe pump (KDScientific Inc.) was connected to the flask to add the diisocyanate compound to the catalyst dissolved in the diepoxide compound.
[0162] Example 1:
[0163] LiCl was used according to the phased application plan. DY / D-CH and MDI 1806 were used to synthesize epoxy-terminated polyoxazolidinone prepolymers with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0164] The reactor was loaded with LiCl (504 mg, 11.9 mmol), MDI 1806 (141 g, 1.13 mol isocyanate groups), and... DY / D-CH (344 g, 2.82 mol epoxy groups). The reactor was shut off and inertized with argon. The mixture was stirred (400 rpm) and heated to 175 °C. After 3.5 hours, the reaction mixture was allowed to cool to room temperature. The result was determined by the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum of the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0165] The following analysis data was obtained:
[0166] EEW: 369g / eq
[0167] Oxazolidinone content: 20.0% by weight
[0168] Number average molecular weight: 697 g·mol -1
[0169] Polydispersion index: 2.9
[0170] Color index: Gardner scale 7
[0171] Viscosity: 120000 mPa·s
[0172] Example 2:
[0173] According to the semi-batch protocol, LiBr and DMPU are used in a 1:1 (weight / weight) ratio. Epoxy-terminated polyoxazolidinone prepolymers were synthesized using DY / D-CH, ipox RD 20, and MDI 1806, with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0174] Loading into the reactor as described above A mixture of DY / D-CH (190 g, 1.56 mol epoxy groups) and ipox RD 20 (190 g, 1.27 mol epoxy groups) was prepared. The reactor was shut off and inertized with argon. The mixture was stirred (400 rpm) and heated to 175 °C. A solution of LiBr (25 mg, 0.29 mmol) in 10 mL of DMPU was added in one go. After 10 minutes at this temperature, MDI 1806 (141 g, 1.13 mol isocyanate groups) was added at a rate of 1.6 mL / min. After the addition was complete, the mixture was stirred at 175 °C for 3 hours, and then allowed to cool to room temperature. The results were obtained by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum of the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0175] The following analysis data was obtained:
[0176] EEW: 303g / eq
[0177] Number average molecular weight: 903 g·mol -1
[0178] Polydispersion index: 3.8
[0179] Color index: Gardner scale 4.8
[0180] Viscosity: 594000 mPa·s
[0181] Example 3:
[0182] According to the semi-batch protocol, LiBr and DMPU are used in a 2:1 (weight / weight) ratio. Epoxy-terminated polyoxazolidinone prepolymers were synthesized using DY / D-CH, ipox RD 20, and MDI 1806, with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0183] Loading into the reactor as described above A mixture of DY / D-CH (250 g, 2.05 mol epoxy groups) and ipox RD 20 (125 g, 0.83 mol epoxy groups) was prepared. The reactor was shut off and inertized with argon. The mixture was stirred (400 rpm) and heated to 175 °C. A solution of LiBr (25 mg, 0.29 mmol) in 8.3 mL of DMPU was added in one go. After 10 minutes at this temperature, MDI 1806 (144 g, 1.15 mol isocyanate groups) was added at a rate of 1.8 mL / min. After the addition was complete, the mixture was stirred at 175 °C for 3 hours, and then allowed to cool to room temperature. The results were obtained by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum of the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0184] The following analysis data was obtained:
[0185] EEW: 298g / eq
[0186] Number average molecular weight: 794 g·mol -1
[0187] Polydispersion index: 3.4
[0188] Color index: 7.6 on the Gardner scale.
[0189] Viscosity: 202000 mPa·s
[0190] Example 4:
[0191] According to the semi-batch protocol, LiBr and DMPU are used in a 1:2 (weight / weight) ratio. Epoxy-terminated polyoxazolidinone prepolymers were synthesized using DY / D-CH, ipox RD 20, and MDI 1806, with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0192] Loading into the reactor as described above A mixture of DY / D-CH (125 g, 1.02 mol epoxy groups) and ipox RD 20 (250 g, 1.67 mol epoxy groups) was prepared. The reactor was shut off and inertized with argon. The mixture was stirred (400 rpm) and heated to 175 °C. A solution of LiBr (23 mg, 0.26 mmol) in 7.8 mL of DMPU was added in one go. After 10 minutes at this temperature, MDI 1806 (135 g, 1.08 mol isocyanate groups) was added at a rate of 1.8 mL / min. After the addition was complete, the mixture was stirred at 175 °C for 3 hours, and then allowed to cool to room temperature. The results were obtained by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum of the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0193] The following analysis data was obtained:
[0194] EEW: 308g / eq
[0195] Number average molecular weight: 955 g·mol -1
[0196] Polydispersion index: 3.6
[0197] Color index: Gardner scale 6
[0198] Viscosity: 1080000 mPa·s
[0199] Example 5:
[0200] According to the semi-batch scheme, LiBr and DMPU are used... DY / D-CH and pMDI were used to synthesize epoxy-terminated polyoxazolidinone prepolymers with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0201] Loading into the reactor as described above DY / D-CH (350 g, 2.87 mol epoxy groups). The reactor was shut off and inert with argon. The mixture was stirred (400 rpm) and heated to 185 °C. A solution of LiBr (25 mg, 0.29 mmol) in 8.3 mL of DMPU was added in one go. After 10 minutes at this temperature, pMDI (152 g, 1.15 mol isocyanate groups) was added at a rate of 1.5 mL / min. After the addition was complete, the mixture was stirred at 180 °C for 2 hours, then allowed to cool to room temperature. The result was determined by the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum of the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹.-1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0202] The following analysis data was obtained:
[0203] EEW: 330g / eq
[0204] Number average molecular weight: 817 g·mol -1
[0205] Polydispersion index: 8.9
[0206] Color index: 8.1 on the Gardner scale
[0207] Viscosity: 513000 mPa·s
[0208] Example 6:
[0209] According to the semi-batch method, LiBr and CPC are used in a 1:1 (weight / weight) ratio. Epoxy-terminated polyoxazolidinone prepolymers were synthesized using DY / D-CH, ipox RD 20, and MDI and pMDI in a 1:1 (weight / weight) ratio, with an epoxy group to isocyanate group molar ratio of 2.5:1.
[0210] Loading into the reactor as described above DY / D-CH (75 g, 614.8 mmol epoxy groups). The reactor was shut off and inert with argon. The mixture was stirred (400 rpm) and heated to 185 °C. A solution of LiBr (9.6 mg, 0.11 mmol) in 34.9 mL of CPC was added in one go. ipox RD20 (75 g, 500 mmol epoxy groups) was added to the mixture. After 10 minutes at this temperature, a mixture of MDI (29.45 g, 223 mmol isocyanate groups) and pMDI (27.9 g, 223 mmol isocyanate groups) was added at a rate of 1.2 mL / min. After the addition was complete, the mixture was stirred at 185 °C for 1 hour, then allowed to cool to room temperature. The analysis was performed by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum from the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0211] The following analysis data was obtained:
[0212] EEW: 362g / eq
[0213] Number average molecular weight: 904 g·mol -1
[0214] Polydispersion index: 9.5
[0215] Color index: Gardner scale 6.3
[0216] Viscosity: 88700 mPa·s
[0217] Example 7:
[0218] According to the semi-batch method, LiBr and CPC are used in a 1:1 (weight / weight) ratio. DY / D-CH, ipox RD 20 and MDI were used to synthesize epoxy-terminated polyoxazolidinone prepolymers with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0219] Loading into the reactor as described above DY / D-CH (95 g, 778.7 mmol epoxy groups). The reactor was shut off and inert with argon. The mixture was stirred (400 rpm) and heated to 185 °C. A solution of LiBr (12 mg, 0.14 mmol) in 3.4 mL of CPC was added in one go. Ipox RD20 (95 g, 633.3 mmol epoxy groups) was added to the mixture. After 10 minutes at this temperature, MDI (70.72 g, 564.8 mmol isocyanate groups) was added at a rate of 1.2 mL / min. After the addition was complete, the mixture was stirred at 185 °C for 1 hour, then allowed to cool to room temperature. The analysis was performed by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum from the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0220] The following analysis data was obtained:
[0221] EEW: 292g / eq
[0222] Number average molecular weight: 838 g·mol -1
[0223] Polydispersion index: 5.3
[0224] Color index: 7.1 on the Gardner scale
[0225] Viscosity: 714000 mPa·s
[0226] Example 8:
[0227] According to the semi-batch protocol, LiBr and CPC are used in a 2:1 (weight / weight) ratio. DY / D-CH, ipox RD 20 and pMDI were used to synthesize epoxy-terminated polyoxazolidinone prepolymers with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0228] Loading into the reactor as described above DY / D-CH (100 g, 819.7 mmol epoxy groups). The reactor was shut off and inert with argon. The mixture was stirred (400 rpm) and heated to 185 °C. A solution of LiBr (10.4 mg, 0.12 mmol) in 52 mL of CPC was added in one go. Ipox RD20 (50 g, 333.3 mmol) was added to the mixture. After 10 minutes at this temperature, pMDI (61 g, 461.2 mmol isocyanate groups) was added at a rate of 1.2 mL / min. After the addition was complete, the mixture was stirred at 185 °C for 1 hour, then allowed to cool to room temperature. The analysis was performed by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum from the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0229] The following analysis data was obtained:
[0230] EEW: 379g / eq
[0231] Number average molecular weight: 907 g·mol -1
[0232] Polydispersion index: 14.5
[0233] Color index: Gardner scale 6.1
[0234] Viscosity: 28100 mPa·s
[0235] Example 9:
[0236] According to the semi-batch method, LiBr and CPC are used in a 1:1 (weight / weight) ratio. DY / D-CH, ipox RD 20, and MDI and pMDI were used to synthesize epoxy-terminated polyoxazolidinone prepolymers with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0237] Loading into the reactor as described above DY / D-CH (75 g, 614.8 mmol epoxy groups). The reactor was shut off and inert with argon. The mixture was stirred (400 rpm) and heated to 185 °C. A solution of LiBr (9.5 mg, 0.11 mmol) in 34.9 mL of CPC was added in one go. ipox RD20 (75 g, 500 mmol) was added to the mixture. After 10 minutes at this temperature, a mixture of MDI (37.19 g, 297.3 mmol isocyanate groups) and pMDI (19.63 g, 148.6 mmol isocyanate groups) was added at a rate of 1.2 mL / min. After the addition was complete, the mixture was stirred at 185 °C for 3.5 hours, then allowed to cool to room temperature. The results were obtained by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum of the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0238] The following analysis data was obtained:
[0239] EEW: 286g / eq
[0240] Number average molecular weight: 871 g·mol -1
[0241] Polydispersion index: 8.0
[0242] Color index: Gardner scale 8.3
[0243] Viscosity: 48500 mPa·s
[0244] Example 10:
[0245] According to the semi-batch method, LiBr and CPC are used in a 1:1 (weight / weight) ratio. DY / D-CH, ipox RD 20, and MDI and pMDI were used to synthesize epoxy-terminated polyoxazolidinone prepolymers with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0246] Loading into the reactor as described above DY / D-CH (150 g, 1.23 mmol epoxy groups). The reactor was shut off and inert with argon. The mixture was stirred (400 rpm) and heated to 185 °C. A solution of LiBr (18 mg, 0.22 mmol) in 6.9 mL of CPC was added in one go. ipox RD20 (150 g, 1.00 mmol) was added to the mixture. After 10 minutes at this temperature, a mixture of MDI (74.38 g, 594.4 mmol isocyanate groups) and pMDI (39.26 g, 297.3 mmol isocyanate groups) was added at a rate of 1.2 mL / min. After the addition was complete, the mixture was stirred at 185 °C for 3.5 hours, then allowed to cool to room temperature. The results were obtained by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum of the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0247] The following analysis data was obtained:
[0248] EEW: 379g / eq
[0249] Number average molecular weight: 875 g·mol -1
[0250] Polydispersity index: 7.6
[0251] Color index: Gardner scale 5.2
[0252] Viscosity: Undetectable, sample viscosity is too high.
[0253] Example 11:
[0254] According to a semi-batch method, epoxide-terminated polyoxazolidinone prepolymers were synthesized using Ph4PCl with Araldite DY / D-CH, ipox RD20, MDI, and pMDI in a 1:1 (weight / weight) ratio, with a molar ratio of epoxy groups to isocyanate groups of 2.5:1.
[0255] Araldite DY / D-CH (150 g, 1.23 mmol epoxy groups) was loaded into the reactor as described above. The reactor was shut off and inertized with argon. The mixture was stirred (400 rpm) and heated to 185 °C. Ph4PCl (83 mg, 0.22 mmol) was added in one go. ipox RD20 (150 g, 1.00 mmol) was added to the mixture. After 10 minutes at this temperature, a mixture of MDI (74.38 g, 594.4 mmol isocyanate groups) and pMDI (39.26 g, 297.3 mmol isocyanate groups) was added at a rate of 1.2 mL / min. After the addition was complete, the mixture was stirred at 185 °C for 3.5 hours, and then allowed to cool to room temperature. The results were obtained by observing the absence of an isocyanate band (2260 cm⁻¹) in the infrared spectrum of the reaction mixture. -1 The reaction was confirmed to be complete. The infrared spectrum was observed at 1749 cm⁻¹. -1 The characteristic signal of the carbonyl group of oxazolidinone was observed at the site.
[0256] The measured EEW was 276 g / eq.
[0257] Oxazolidinone content: 18.5% by weight
[0258] GPC analysis showed a molecular weight of 875 g·mol⁻¹. -1 The number-average molecular weight and polydispersity index of 7.6.
[0259] The color index was measured to be 5.6 on the Gardner scale.
[0260] Viscosity: Undetectable, sample viscosity is too high.
[0261] Comparative Example 12: BDDE + Aradur 949-2 (70:30)
[0262] 14.0 g of BDDE was added to 10.9 g of Aradur 949-2 and 1.6 g of a 10 wt% solution of phosphorous acid (diluted in 1-methoxy-2-propanol). This corresponds to a 70:30 BDDE / Aradur 949-2 (solid / solid) mixing ratio. The concentration of the catalyst used was 0.8 wt% based on solid content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellow-green and slightly turbid, with a shelf life well over 24 hours.
[0263] Comparative Example 13: TMPGE + Aradur 949-2 (70:30)
[0264] 14.0 g of TMPGE was added to 10.9 g of Aradur 949-2 and 1.6 g of a 10 wt% solution of phosphorous acid (diluted in 1-methoxy-2-propanol). This corresponds to a mixing ratio of 70:30 TMPGE / Aradur 949-2 (solid / solid). The concentration of the catalyst used was 0.8 wt% based on solid content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellow-green and slightly turbid, with a shelf life well over 24 hours.
[0265] Comparative Example 14: GT 6009N+Aradur 949-2(80∶20)
[0266] 8 grams GT 6009N was mixed with a solvent solution of 5.1 g MPA, 5.1 g toluene, and 0.40 g butanol. This was then added to a solution of 3.6 g Aradur 949-2 and 0.8 g 10% by weight phosphorous acid (diluted in 1-methoxy-2-propanol). This corresponds to an 80:20 ratio. The mixing ratio of GT 6009N / Aradur 949-2 (solid / solid). The concentration of the catalyst used was 0.8% by weight based on solid content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellow-green and slightly turbid, with a shelf life well over 24 hours.
[0267] Comparative Example 15: GT 6009N+Aradur 949-2(75∶25)
[0268] 7.5 grams GT 6009N was mixed with a solvent solution of 4.9 g MPA, 4.9 g toluene (Toluol), and 0.40 g butanol. This was then added to a solution of 4.5 g Aradur 949-2 and 0.8 g 10 wt% phosphorous acid (diluted in 1-methoxy-2-propanol). This corresponds to a 75:25 ratio. The mixing ratio of GT 6009N / Aradur 949-2 (solid / solid). The concentration of the catalyst used was 0.8% by weight based on solid content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellow-green and slightly turbid, with a shelf life well over 24 hours.
[0269] Comparative Example 16: GT 6009 N+Aradur 3380-1CH(85∶15)
[0270] Will Add GT 6009 N to a glass vial and dilute with an equal volume of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. Seal the vial and store it in an oven at 50°C. The resulting solution is stable for several months before use. Add 17 g of 50% N... GT 6009 N solution was added to 3 g of Aradur 949-2 and 0.8 g of 10 wt% phosphorous acid solution (diluted in 1-methoxy-2-propanol). This corresponds to an 85:15 ratio. The mixing ratio of GT 6009N / Aradur 3380-1 CH (solid / solid) was determined. Additionally, 5 g of a solvent solution of MPA:toluene:butanol in a 1:1:1 ratio was added. The catalyst concentration used was 0.8% by weight based on solid content. This formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellow-green and slightly turbid, with a shelf life well over 24 hours.
[0271] Comparative Example 17: GT 6009 N+Aradur 3380-1CH(85∶15)
[0272] Will Add GT 6009 N to a glass vial and dilute with an equal volume of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. Seal the vial and store it in an oven at 50°C. The resulting solution is stable for several months before use. Add 17 g of 50% N... GT 6009 N solution was added to 3 g of Aradur 949-2 and 0.8 g of 10 wt% phosphorous acid solution (diluted in 1-methoxy-2-propanol). This corresponds to an 85:15 ratio. The mixing ratio of GT 6009N / Aradur 3380-1 CH (solid / solid) was determined. Additionally, 5 g of a solvent solution of MPA:toluene:butanol in a 1:1:5 ratio was added. The catalyst concentration used was 0.8% by weight based on solid content. This formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellow-green and slightly turbid, with a shelf life well over 24 hours.
[0273] Example 18: Crosslinking of the product of Example 1
[0274] The product of Example 1 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 13 g of 50% GLM 123 solution was added to 6.37 g of Aradur 949-2 and 0.8 g of 10% by weight phosphorous acid solution (diluted in 1-methoxy-2-propanol). This corresponds to a mixing ratio of 65:35 GLM 123 / Aradur 949-2 (solid / solid). The catalyst concentration was 0.8% by solids content. The resulting solution was yellowish-brown and slightly turbid, with a pot life well over 24 hours. The oxazolidinone content was 12.4% by weight.
[0275] Example 19: Product of Example 3 + Aradur 949-2 (70:30)
[0276] The product of Example 3 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C. The resulting solution was stable for several months before use. 14.0 g of this solution was added to 5.5 g of Aradur 949-2 and 0.8 g of a 10% by weight solution of phosphorous acid (diluted in 1-methoxy-2-propanol). This corresponds to a mixing ratio of 70:30 product of Example 3 / Aradur 949-2 (solid / solid). The concentration of the catalyst used was 0.8% by weight based on solid content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellow-green and slightly turbid, with a shelf life well over 24 hours.
[0277] Example 20: Product of Example 2 + Aradur 949-2 (70:30)
[0278] The product of Example 2 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 14.0 g of this solution was added to 5.5 g of Aradur 949-2 and 0.8 g of a 10% by weight solution of phosphorous acid (diluted in 1-methoxy-2-propanol). This corresponds to a mixing ratio of 70:30 product of Example 2 / Aradur 949-2 (solid / solid). The catalyst concentration was 0.8% by weight based on solid content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellowish-brown and slightly turbid, with a shelf life well over 24 hours.
[0279] Example 21: Product of Example 4 + Aradur 949-2 (70:30)
[0280] The product of Example 4 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 14.0 g of this solution was added to 5.5 g of Aradur 949-2 and 0.8 g of a 10% by weight solution of phosphorous acid (diluted in 1-methoxy-2-propanol). This corresponds to a mixing ratio of 70:30 product of Example 4 / Aradur 949-2 (solid / solid). The catalyst concentration was 0.8% by weight based on solids content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellowish-brown and slightly turbid, with a shelf life well over 24 hours.
[0281] Example 22: Product of Example 2 (BDDE∶TMPGE 1∶1 in polymer and MDI) + Aradur 3380-1CH (85∶15)
[0282] The product of Example 2 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 17 g of this solution was added to 3 g of Aradur 3380-1 CH and 0.8 g of 10% by weight phosphorous acid solution (diluted in 1-methoxy-2-propanol). 1.67 g of n-butanol was also added. This corresponds to a mixing ratio of 85:15 product of Example 2 / Aradur 3380-1 CH (solid / solid). The catalyst concentration was 0.8% by weight based on solid content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellowish-brown and slightly turbid, with a shelf life well over 24 hours.
[0283] Example 23: Product of Example 8 + Aradur 3380-1CH (85:15)
[0284] The product of Example 8 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 17 g of this solution was added to 3 g of Aradur 3380-1 CH and 0.8 g of 10% by weight phosphorous acid solution (diluted in 1-methoxy-2-propanol). 1.67 g of n-butanol was also added. This corresponds to a mixing ratio of 85:15 product of Example 8 / Aradur 3380-1 CH (solid / solid). The catalyst concentration was 0.8% by weight based on solids content. The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellowish-brown and slightly turbid, with a shelf life well over 24 hours.
[0285] Example 24: Product of Example 8 + Aradur 3380-1CH (85:15)
[0286] The product of Example 8 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 17 g of this solution was added to 3 g of Aradur 3380-1 CH. 1.67 g of n-butanol was also added. This corresponds to a mixing ratio of 85:15 product of Example 8 / Aradur 3380-1 CH (solid / solid). The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellowish-brown and slightly turbid, with a shelf life well over 24 hours.
[0287] Example 25: Product of Example 9 + Aradur 3380-1CH (85:15)
[0288] The product of Example 9 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 17 g of a solution of 50% by weight of the product of Example 9 was added to 3 g of Aradur 3380-1 CH. 1.67 g of n-butanol was also added. This corresponds to a mixing ratio of 85:15 product of Example 9 / Aradur 3380-1 CH (solid / solid). The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellowish-brown and slightly turbid, with a shelf life well over 24 hours.
[0289] Example 26: Product of Example 10 + Aradur 3380-1CH (85:15)
[0290] The product of Example 10 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 17 g of a solution of 50% by weight of the product of Example 10 was added to 3 g of Aradur 3380-1 CH. 1.67 g of n-butanol was also added. This corresponds to a mixing ratio of 85:15 product of Example 10 / Aradur 3380-1 CH (solid / solid). The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellowish-brown and slightly turbid, with a shelf life well over 24 hours.
[0291] Example 27: Product of Example 11 + Aradur 3380-1CH (85:15)
[0292] The product of Example 11 was added to a glass vial and diluted with the same amount of a solvent mixture consisting of 12 parts by weight of methoxypropyl acetate, 12 parts by weight of toluene, and 1 part by weight of n-butanol. The vial was sealed and stored in an oven at 50°C for 16 hours. The resulting solution was stable for several months. 17 g of a solution of 50% by weight of the product of Example 11 was added to 3 g of Aradur 3380-1 CH. 1.67 g of n-butanol was also added. This corresponds to a mixing ratio of 85:15 product of Example 11 / Aradur 3380-1 CH (solid / solid). The formulation was mixed in a high-speed mixer at 2850 rpm for 30 seconds. The resulting solution was yellowish-brown and slightly turbid, with a shelf life well over 24 hours.
[0293] The content of oxazolidinone is 13.5% by weight.
[0294] application
[0295] Apply the formulation to a tin-plated plate (E1) measuring 250 x 200 x 0.24 mm³. The tin-plated plate should be thoroughly cleaned and degreased, for example, with ethyl acetate or acetone, before coating. Apply the coating using a 0.7-meter spiral applicator (equivalent to 42 μm wet). Ensure the white plate is coated as completely as possible with this spiral applicator. After application and approximately 5 minutes of ventilation time, cure the coating in an air oven at 200°C for 12 to 20 minutes, depending on the crosslinking agent used. The cured dry layer thickness should be 10 μm.
[0296] Table 1: Experimental Results
[0297]
[0298] CE Comparative Example
[0299] Table 2: Experimental Results
[0300]
[0301] CE Comparison
[0302] Comparative Example 28:
[0303] According to the batch synthesis scheme, epoxy-terminated polyoxazolidinone prepolymers were synthesized using LiCl with Araldite DY / D-CH and MDI 1806, with a molar ratio of epoxy groups to isocyanate groups of 2:1.
[0304] LiCl (0.052 g, 1.23 mmol), MDI 1806 (22.0 g, 88 mmol), and AralditeDY-D / CH (35.6 g, 176 mmol) were loaded into a reactor as described above (see the section preceding “Example 1”). The reactor was shut off and inertized with argon. The mixture was stirred (400 rpm) and heated to 175 °C. After 10 minutes, the reaction was stopped as the reaction mixture solidified.
[0305] The characteristic signal of the carbonyl group of oxazolidinone was observed at 1749 cm⁻¹ in the infrared spectrum, along with many other peaks indicating byproducts.
[0306] It is impossible to determine EEW.
[0307] It is impossible to analyze molecular weight using GPC.
[0308] The color index was measured to be >18, and therefore exceeded the range of the Gardner scale.
Claims
1. A composition comprising at least (A) At least one epoxy group-terminated polyoxazolidinone derived from at least one polyisocyanate compound and at least one aliphatic polyepoxide compound. (B) A compound having at least one group reactive to a terminal epoxy group, and (C) At least one solvent, The molar ratio of the epoxy group of the polyepoxide compound to the isocyanate group of the polyisocyanate compound is from 50:1 to 2.4:
1. The at least one epoxy group-terminated polyoxazolidinone is present in an amount of 50 to 95% by weight, based on the solid content of the composition. The at least one compound having at least one terminal epoxy group is present in an amount of 5 to 50% by weight, based on the solid content of the composition, and the weight ratio of the epoxy group of component (A) to the terminal epoxy group of component (B) is 50:50 to 95:
5. The total of all components, based on the solid content of the composition, is 100% by weight. The composition has a solid content of at least 35% by weight.
2. The composition according to claim 1, wherein the at least one solvent (C) is at least one organic solvent selected from aromatic hydrocarbons, ketones, alcohols, ether alcohols and their acetates, cyclic ethers, ureas and mixtures thereof.
3. The composition according to claim 1 or 2, wherein the molar ratio of the epoxy group of the polyepoxide compound to the isocyanate group of the polyisocyanate compound is from 50:1 to 2.5:
1.
4. The composition according to claim 3, wherein the molar ratio of the epoxy group of the polyepoxide compound to the isocyanate group of the polyisocyanate compound is 25:1 to 2.5:
1.
5. The composition according to claim 4, wherein the molar ratio of the epoxy group of the polyepoxide compound to the isocyanate group of the polyisocyanate compound is from 10:1 to 2.5:
1.
6. The composition according to claim 1, wherein component (B) is selected from dicyandiamide, substituted guanidine, phenolic compounds, aliphatic amines, benzoxazine, acid anhydrides, aminoamines, polyamides, polyamines, polyesters, polyisocyanates, polythiols, urea-formaldehyde, melamine-formaldehyde resins, and mixtures thereof.
7. The composition according to claim 1, wherein the at least one polyisocyanate compound is at least one aliphatic polyisocyanate compound and / or at least one aromatic polyisocyanate compound.
8. The composition according to claim 1, wherein the at least one polyisocyanate compound is at least one aromatic polyisocyanate compound.
9. The composition according to claim 1, wherein the at least one epoxy group-terminated polyoxazolidinone (A) has an epoxy equivalent weight (EEW) of 100 g / eq to 10000 g / eq, wherein the epoxy equivalent weight is determined by titration according to DIN EN 1877-1:2000.
10. The composition according to claim 9, wherein the at least one epoxy group-terminated polyoxazolidinone (A) has an epoxy equivalent weight (EEW) of 150 g / eq to 6000 g / eq.
11. The composition according to claim 10, wherein the at least one epoxy group-terminated polyoxazolidinone (A) has an epoxy equivalent weight (EEW) of 200 g / eq to 2000 g / eq.
12. The composition according to claim 1, wherein the epoxy group-terminated polyoxazolidinone has an oxazolidinone content of 5 to 50% by weight.
13. The composition of claim 12, wherein the epoxy group-terminated polyoxazolidinone has an oxazolidinone content of 7 to 45% by weight.
14. The composition of claim 13, wherein the epoxy group-terminated polyoxazolidinone has an oxazolidinone content of 10 to 40% by weight.
15. The composition according to claim 1 or 2, wherein at least one solvent (C) is present in the composition in an amount of 5 to 75% by weight relative to the sum of components (A), (B) and (C) of the composition.
16. A method for preparing a composition according to any one of claims 1 to 15, comprising at least the step of mixing components (A), (B) and (C).
17. The composition obtainable by the method according to claim 16.
18. Use of the composition according to any one of claims 1 to 15 or 17 as a coating formulation.
19. Use of the composition according to any one of claims 1 to 15 or 17 as an anti-corrosion coating formulation.
20. Use of the composition according to any one of claims 1 to 15 or 17 as a protective coating formulation.
21. Use of the composition according to any one of claims 1 to 15 or 17 as a can coating formulation or as a coil coating formulation.
22. A coating formulation comprising at least the composition according to any one of claims 1 to 15 or 17.
23. A method of coating a substrate, comprising the step of applying the coating formulation according to claim 22 onto the substrate.
24. A coating substrate comprising the coating formulation according to claim 22.
Citation Information
Patent Citations
process for producing color and / or effect coatings
DE10043405C1
Process for the production of physiologically harmless mono- or polyisocyanates with a low vapor pressure
DE1090196A
Process for preparing oxadiazinones with free isocyanate groups
DE1670666A
process for the trimerization of aromatic polyisocyanates
DE1670667A
Process for the production of polymeric organic isocyanates
DE1954093A1